Rancang Bangun Modul Kontrol Alat Terapi Batu Ginjal (ESWL) Dengan Mikrokontroler AT-Mega16 Berdasarkan Sistem Pernapasan Manusia - Wahyudi, Bayu; Cipta, Kusuma Adi; Nuha ABA, Muhammad Ulin (Universitas Semarang, 2020)
Extracorporeal shockwave lithotripsy (ESWL) is the most cost effective treatment option in cases of kidney stones. ESWL uses an energy source called lithotriptor to produce a shock wave that is high in electromagnetic energy in pulses to break down rocks into fine grains of sand and come out naturally with urine. In this study the authors modified the control of the ESWL unit by adding an automatic wave shooting system based on respiration from therapeutic patients using the MPXV7002DP sensor and the ATmega16 microcontroller and applying the 16x2 LCD as a display.The maximum reading capability of this module is 9000 times the active relay, which means that ESWL can shoot as many as 9000 times automatically according to human breathing. This automatic kidney stone therapy module can shoot as many as 3 waves in one breath. Has created a number of inspiration counters and the number of wave shots that ESWL has fired into kidney stone therapy patients.